THE PHILOSOPHY OF SPIRITS PURIFICATION IN THE RITUAL ENTAS-ENTAS IN WONOTORO VILLAGE AS THE IDENTITY OF THE TENGGER COMMUNITY - Setyani, Turita Indah; Pudjiastuti, Titik; Suharjo, Rias; Buduroh, Mamlahatun; Mu’jizah, Mu’jizah; Rahmawanto, Dwi (UI Scholars Hub, 2024)
This paper examines the Ritual Entas-entas as a purification ceremony for spirits in Wonotoro Village, Tengger. The ritual originates from a manuscript believed to aid in purifying the spirits of deceased family members. This ritual has been passed down orally. However, the manuscript serving as the reference for the ritual can no longer be traced. The issue is, how the sustainability of the Ritual Entas-entas in Wonotoro Village, Tengger? The research aims to demonstrate that the Tengger community possesses a collective memory strength and high adherence to traditional rules as part of everyday religious practice. The research utilizes ethnographic methodology along with the theory of collective memory from the Javanese religious perspective to address the problem and validate the research objectives. Initial findings indicate that: 1) The Ritual Entas-entas in Wonotoro Village is an oral tradition derived from written tradition; 2) The Ritual Entas-entas is a collective memory highly believed to possess the power to facilitate the purification of one's spirit to return to the Almighty Creator, thus it is deemed essential; 3) The Tengger community demonstrates a high level of devotion to the Almighty Creator. From these findings, it can be concluded that the Tengger community, particularly in Wonotoro Village, retains relevant ethnoscience to this day.